ANALYSIS OF SHARIA ECONOMIC DEVELOPMENT THROUGH THE ROLE OF NATURAL RESOURCES AND HUMAN RESOURCES IN SURABAYA - Salsabila, Naura Zhalfa; Hurin In, Nazilah; Haq, Wahyu Fajar Dhiyaul (Journal of Finance, Economics and Business, 2024)
Economic development is a serious concern. darkness that has received a lot of applied enlightenment. The government and nation are striving to implement the understanding of reform. In providing quality human resources, it is important to instill a religious basis and expertise. When these two things become a guide, quality human resources will emerge. In the context of Surabaya, the role of natural resources is also relevant. However, this research emphasizes the role of human resources as the main key in strengthening the Sharia economy. By combining religious knowledge and expertise, human resources can contribute significantly to economic development based on the principles of Islamic principles.